L’anxiété nuisible chez les apprenants du FLE. Le cas des étudiants de la philologie romane en cycle de licence - Blachowska-Szmigiel, Marzena (Glottodidactica, 2020)
Language anxiety is the feeling of tension and apprehension associated with second / foreign language learning. It manifests itself in two types of emotional reactions: positive (positive anxiety) and negative (debilitating anxiety). The focus of this article is to explore the debilitating language anxiety of students learning French as a foreign language and to find out its level in the first, second and third years of undergraduate studies in Romance philology. The main research problem concerns the need to develop their ability to manage debilitating language anxiety. For this purpose, the findings of a FLCAS questionnaire are presented.